2009
DOI: 10.1302/0301-620x.91b7.22013
|View full text |Cite
|
Sign up to set email alerts
|

The Morscher Press Fit acetabular component

Abstract: We reviewed the results at nine to 13 years of 125 total hip replacements in 113 patients using the monoblock uncemented Morscher press-fit acetabular component. The mean age at the time of operation was 56.9 years (36 to 74). The mean clinical follow-up was 11 years (9.7 to 13.5) and the mean radiological follow-up was 9.4 years (7.7 to 13.1). Three hips were revised, one immediately for instability, one for excessive wear and one for deep infection. No revisions were required for aseptic loosening. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…In that study, no radiolucencies were seen around the cups, whereas osteolytic defects were found around 8% of the stems investigated. Similarly encouraging results were described after a minimum of 9 years follow-up of 125 THAs using the Morscher cup, where none of the cups were revised because of aseptic loosening or osteolysis, and 3 were revised for other reasons (Gwynne-Jones et al 2009). Berli et al (2007) reported the 15-year results of 280 hips implanted with the Morscher cup, quoting a survival of 98% for aseptic loosening and 95% overall.…”
Section: Discussionsupporting
confidence: 55%
“…In that study, no radiolucencies were seen around the cups, whereas osteolytic defects were found around 8% of the stems investigated. Similarly encouraging results were described after a minimum of 9 years follow-up of 125 THAs using the Morscher cup, where none of the cups were revised because of aseptic loosening or osteolysis, and 3 were revised for other reasons (Gwynne-Jones et al 2009). Berli et al (2007) reported the 15-year results of 280 hips implanted with the Morscher cup, quoting a survival of 98% for aseptic loosening and 95% overall.…”
Section: Discussionsupporting
confidence: 55%
“…As for many other contemporary designs and articulations, mostly medium-term results are available for monobloc cups (Hinrichs et al 2001, Unger et al 2005, Malizos et al 2008, Gwynne-Jones et al 2009). However, problems due to osteolysis and wear rarely result in revision surgery until 6–8 years have elapsed; thus, optimistic reports on the survival of monobloc cups must be regarded with some caution.…”
Section: Discussionmentioning
confidence: 99%
“…Even today, the focus is on the articulating surfaces and materials with the hope that recent technology will solve these problems. Numerous uncemented implants with different appearances have indeed shown excellent results in small or medium-sized cohorts (Badhe et al 2002, Gabbar et al 2008, Reigstad et al 2008, Aldinger et al 2009, Gwynne-Jones et al 2009), in contrast to older designs with unacceptable failure rates (Puolakka et al 1999, Thanner et al 1999, Lai et al 2002). …”
Section: Introductionmentioning
confidence: 99%
“…Finally, osteolysis around the acetabulum was intentionally not addressed in this study for two reasons. One, it was systematically looked for and not found in a single patient, and two, osteolysis has rarely been reported with the use of the Morscher cup 31–33…”
Section: Discussionmentioning
confidence: 99%